Challenges and opportunities in score reporting: a panel of personal perspectives - Brown, Gavin T. L.; Kannan, Priya; Sinharay, Sandip; Zapata-Rivera, Diego; Zenisky, April L. (Frontiers in Education, 2023)
The field of score reporting continues to evolve because of new challenges, opportunities, and needs of society (e.g., COVID, remote teaching and learning). In this paper, the new challenges and opportunities in score reporting are discussed from the personal perspective of four experts who have previously conducted research in designing score reports in education. Comments are organised around four key questions concerning challenges raised by the Covid pandemic, how research will change, what current research is being conducted, and new directions in the field of score reporting.